Commuters’ travel characteristics, modal choice and performance of public transport options in Lagos, Nigeria / Wale Alade, Mobolaji Olaseni and Olufemi Adeniji. - Alade, Wale; Olaseni, Mobolaji; Adeniji, Olufemi (Faculty of Architecture, Planning and Surveying Universiti Teknologi MARA, Shah Alam, 2019)
In the past decade-plus there has been a paucity of comparative studies of the performance of public transport options in Lagos. This study evaluates commuters’ access to public transport modes (yellow bus, BRT and ferry), trip characteristics, factors influencing choice of, and the performance of each mode in Lagos to establish improvement priorities. Research data was obtained from 124 commuters through close-ended questionnaire at selected terminals on a major corridor during the morning peak period using incidental sampling technique. The performance of public transport modes was measured using seven variables on a 5-point rating scale. Analysis of variance show significant variation in commuters’ trip cost to terminals. The BRT is the most affordable with respect to fare but has the worst boarding delay occurrence, the ferry is the most efficient with respect to trip time while 45% of yellow bus passengers spend more than one hour per trip. From the linear regression results, delay time at the terminals, travel time and travel cost to destinations accounted for about 55.8% of the total variance in the preferred mode of travel. From the relative performance analysis results, the BRT has the highest mean performance index of 3.72, followed by ferry (3.01) and the yellow bus (2.62). These findings facilitate our understanding of factors influencing the performance and choice of public transport modes in Lagos while providing insights into areas needing attention for improvement. Based on these findings, the study recommended the provision of more BRT buses to reduce the waiting time at terminals, and the review of ferry operations to reduce fare and enhance safety and introduce measures to upscale the services of the for better performance. Future studies should explore commuter waiting and comfort at bus stations and terminals and on-board time use.